2017
DOI: 10.1007/s11892-017-0902-3
|View full text |Cite
|
Sign up to set email alerts
|

How Low Can You Go? Reducing Rates of Hypoglycemia in the Non-critical Care Hospital Setting

Abstract: Strategies to reduce hypoglycemia rates should focus on the most common causes of iatrogenic hypoglycemia. Creating a standardized insulin order set with built-in clinical decision support can help reduce rates of hypoglycemia. Coordination of blood glucose monitoring, meal tray delivery, and insulin administration is an important and challenging task. Protocols and processes should be in place to deal with interruptions in nutrition to minimize risk of hypoglycemia. A glucose management page that has all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 67 publications
0
28
0
1
Order By: Relevance
“…Previous studies have reported that increasing age is an independent risk factor for the development of hypoglycemia in insulin-treated patients with type 2 diabetes 4. It has also been shown that elderly patients frequently fail to communicate symptoms of hypoglycemia to hospital staff32 and develop hypoglycemic symptoms at a significantly lower glucose concentration compared with younger patients 33. These factors often lead to more prolonged and more severe hypoglycemia in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that increasing age is an independent risk factor for the development of hypoglycemia in insulin-treated patients with type 2 diabetes 4. It has also been shown that elderly patients frequently fail to communicate symptoms of hypoglycemia to hospital staff32 and develop hypoglycemic symptoms at a significantly lower glucose concentration compared with younger patients 33. These factors often lead to more prolonged and more severe hypoglycemia in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia is a common occurrence in hospitalized patients and is linked to multiple adverse clinical outcomes and mortality. 1 Acute hypoglycemia can provoke cardiac ischemia and arrhythmias, as well as neurologic harm ranging in severity from altered cognition or irritability to focal neurologic deficits, loss of consciousness, stroke, seizures, and coma. 2 Besides these potentially life-threatening complications, hypoglycemia can be a source of patient dissatisfaction and worry.…”
mentioning
confidence: 99%
“… 2 Besides these potentially life-threatening complications, hypoglycemia can be a source of patient dissatisfaction and worry. 1 Approximately half of hypoglycemic events in the hospital are iatrogenic, usually resulting from insulin treatment. 3 In observational studies of hospitalized patients, both spontaneous and iatrogenic hypoglycemia are associated with increased mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Im Verhältnis zur generellen Diabetesprävalenz (7 %) belegen Patienten mit Diabetes mellitus -abhängig von Region und Fokus des Krankenhauses -überproportional viele Akutbetten in Krankenhäusern (8-40 %), wobei nur ein Bruchteil davon primär wegen der Diabeteserkrankung stationär aufgenommen wurde (8 %) [15].…”
Section: Diabetesmanagement Im Krankenhaus -Die Herausforderungunclassified